Singing for lung health in COPD: a multicentre randomised controlled trial of online delivery - William D-C Man; Michael I Polkey; Daisy Fancourt; Winston Banya; Adam Lewis; Nicholas S Hopkinson; Justin L Garner; Keir E J Philip; Matthew J Pavitt; Saeed M Alghamdi; Ali M Alasmari; Edmund Jeffery; et al. (BMJ Open Respiratory Research, 2024)
Background Singing for lung health (SLH) is an arts-based breathing control and movement intervention for people with long-term respiratory conditions, intended to improve symptoms and quality of life. Online, remotely delivered programmes might improve accessibility; however, no previous studies have assessed the effectiveness of this approach.Methods We conducted an assessor-blind randomised controlled trial comparing the impact of 12 weeks of once-weekly online SLH sessions against usual care on health-related quality of life, assessed using the RAND 36-Item Short Form Health Survey (SF-36) Mental Health Composite (MHC) and Physical Health Composite (PHC) scores.Results We enrolled 115 people with stable chronic obstructive pulmonary disease (COPD), median (IQR) age 69 (62–74), 56.5% females, 80% prior pulmonary rehabilitation, Medical Research Council dyspnoea scale 4 (3–4), forced expiratory volume in 1 s % predicted 49 (35–63). 50 participants in each arm completed the study. The intervention arm experienced improvements in physical but not mental health components of RAND SF-36; PHC (regression coefficient (95% CI): 1.77 (95% CI 0.11 to 3.44); p=0.037), but not MHC (0.86 (95% CI −1.68 to 3.40); p=0.504). A prespecified responder analysis based on achieving a 10% improvement from baseline demonstrated a response rate for PHC of 32% in the SLH arm and 12.7% for usual care (p=0.024). A between-group difference in responder rate was not found in relation to the MHC (19.3% vs 25.9%; p=0.403).Discussion and conclusion A 12-week online SLH programme can improve the physical component of quality of life for people with COPD, but the overall effect is relatively modest compared with the impact seen in research using face-to-face group sessions. Further work on the content, duration and dose of online interventions may be useful.Trial registration number NCT04034212.